The Goodrich Sidney Arena, New York World's Fair 1939 (Superior Painting & Lithographing Co)
In the Goodrich Safety Arena Jimmie Lynch and his dare-devil stunt drivers entertain World's Fair visitors comfortably seated in the covered grandstand. In the Goodrich building is a "Rubber Wonderland" where rubber products are manufactured, tested and demonstrated. Located in the Transportation Zone, the Goodrich Safety Arena is across the avenue from the General Motors and Railroad exhibits and across the Grand Central Parkway from the Administration Building